Surface wave driven molecular low pressure plasmas for general lighting (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2016)
Nowadays, compact fluorescent lamps are widely-used in general lighting applications. However, they still struggle with acceptance problems due to the hazardous mercury, which serves as the radiant component inside the lamp. The presented work deals with the development of a mercury-free, electrodeless, low pressure plasma based on a molecular filling and driven by microwaves, which may represent a viable alternative to the conventional CFLs.